Biuletyn Informacyjny KZ NSZZ "Solidarność" . no. 17, 1981 - "Solidarność" FPS "Polmo", [ed. E. Arciszewska et al.] (NSZZ "Solidarność" FPS "Polmo", 1981)
Creation and circulation: For trade-union internal use